Volumetric burden of metastatic lesions drives outcomes in patients with extracranial oligometastatic disease. (20th October 2021) - Cao, Yilin; Chen, Hanbo; Sahgal, Arjun; Erler, Darby; Badellino, Serena; Biswas, Tithi; Dagan, Roi; Foote, Matthew C.; Louie, Alexander V.; Poon, Ian; Ricardi, Umberto; Redmond, Kristin J.
Abstract: Background: We hypothesized that the total volume of metastases at initial oligometastatic (OM) presentation to stereotactic body radiation therapy (SBRT) is an important prognostic factor that can refine the definition of OM disease. Methods: Patients with extracranial oligometastatic cancer (≤5 lesions) treated with SBRT were included in an international multi‐institutional database. Multivariable Cox and competing risks regression models were used to determine the relationship between distant progression‐free survival (DPFS), widespread progression (WSP), and overall survival (OS) with the total planning target volume (PTV) at initial OM presentation to SBRT. All models were adjusted for histology, pre‐SBRT systemic therapy, osseous‐only lesions, and number of metastases. Results: In total, 961 patients were included. The median follow‐up was 24.4 months (IQR: 13.8–37.5). Total PTV had a significant effect on DPFS in the first 18 months after SBRT and was most profound in the first 6 months, when each twofold increase in total PTV conferred a 40.6% increased risk of distant progression ( p < 0.001). Each twofold increase in total PTV increased the risk of WSP by 45.4% in the first 6 months ( p < 0.001). Total PTV had a significant effect on OS in the first 2 years after SBRT, with each twofold PTV change increasing the risk of death by 60.7% during the first 6 months ( p < 0.001) and by 34% thereafter ( p < 0.001). Exploratory gross tumor volume (GTV) analysis confirmed the PTV‐based observations. Conclusion: The total volumetric burden of metastases at initial OM presentation to SBRT is strongly and independently prognostic for the risk of distant and widespread progression and survival. We propose that this metric should drive the definition of OM disease and guide treatment decision‐making. Abstract : This large international, multi‐institutional series of SBRT to extracranial oligometastases demonstrates total volume of metastatic lesions as a strong, independent prognostic factor for cancer outcomes. This metric can redefine oligometastatic disease beyond number of lesions and refine patient selection for an increasingly important treatment paradigm.